Renewable energy: Wind and solar - Brown, Susan P. (Kansas State University, 2009)
One of the goals of a land grant university is to find out the needs of the community and work towards research and programming to meet those needs. The Energy Savings Store has over 5 years of “boots on the ground” experience designing and installing sustainable energy systems for Kansas residents and businesses. We can bring these stories and experiences to this conference, including what barriers we are experiencing in moving to a more sustainable community. Find out about Solar PV, Solar Outdoor Lighting, Solar Hot Water, Solar Air Heating and Wind – which is more affordable and what incentives are available at the state and federal level. View actual installations in Kansas and Missouri and get general cost information.
Keywords: Solar energy; Wind energy; Economic development; Renewable Energy Services Company; Energy Savings Store